Accelerated and Severe Lupus Nephritis Benefits From M1, an Active Metabolite of Ginsenoside, by Regulating NLRP3 Inflammasome and T Cell Functions in Mice - Lin, Tsai-Jung; Wu, Chung-Yao; Tsai, Pei-Yi; Hsu, Wan-Han; Hua, Kuo-Feng; Chu, Ching-Liang; Lee, Yu-Chieh; Chen, Ann; Lee, Sheau-Long; Lin, Yi-Jin; Hsieh, Chih-Yu; Yang, Shin-Ruen; et al. (Frontiers in Immunology, 2019)
Chinese herbal medicines used in combination have long-term been shown to be mild remedies with “integrated effects”. However, our study provides the first demonstration that M1, an active metabolite of ginsenoside, exerted its dramatic therapeutic effects on accelerated and severe lupus nephritis (ASLN) mice, featuring acute renal function impairment, heavy proteinuria, high serum levels of anti-dsDNA, and high-grade, diffuse proliferative renal lesions. In the present study, NZB/WF1 mice were given injections of lipopolysaccharide to induce the ASLN model. M1 (30 mg/kg) was then administered to the mice by gavage daily, and the mice were sacrificed on week 3 and week 5 after the induction of disease. To identify the potential mechanism of action for the pure compound, levels of NLRP3 inflammasome activation in bone marrow-derived dendritic cells (BMDCs), podocytes and macrophages, and antigen-specific T cell activation in BMDCs were determined in addition to mechanistic experiments in vivo. Treatment with M1 dramatically improved renal function, albuminuria and renal lesions and reduced serum levels of anti-dsDNA in the ASLN mice. These beneficial effects with M1 treatment involved the following cellular and molecular mechanistic events: [1] inhibition of NLRP3 inflammasome associated with autophagy induction, [2] modulation of T help cell activation, and [3] induction of regulatory T cell differentiation. M1 improved the ASLN mice by blunting NLRP3 inflammasome activation and differentially regulating T cell functions, and the results support M1 as a new therapeutic candidate for LN patients with a status of abrupt transformation of lower-grade (mild mesangial) to higher-grade (diffuse proliferative) nephritis.